Copper Stress Induces Antioxidant Responses and Accumulation of Sugars and Phytochelatins in Antarctic Colobanthus Quitensis (Kunth) Bartl - Zuniga-Navarro, G; Kohler-Campos, H; Pizarro-Rojas, M; Contreras-Arredondo, R (SOC BIOLGIA CHILE, 2018)
Background: In field, C. quitensis is subjected to many abiotic extreme environmental conditions, such as low temperatures, high UV-B, salinity and reduced water potentials, but not metal or metalloid high concentrations in soil, however, other members of Caryophyllaceae family have tolerance to high concentrations of metals, this is the case of Silene genre. In this work, we hypothesize that C. quitensis have the same mechanisms of Silene to tolerate metals, involving accumulation and induction of antioxidant systems, sugar accumulation and the induction of thiols such as phytochelatins to tolerate. Results: The results showing an effective antioxidant defensive machinery involving non-enzymatic antioxidants such as phenolics, GSH and ascorbic acid, in another hand, GSH-related oligomers (phytochelatins) and sugars was induced as a defensive mechanism. Conclusions: Colobanthus quitensis exhibits certain mechanisms to tolerate copper in vitro demonstrating its plasticity to tolerate several abiotic stress conditions.